Retinoic acid suppresses intestinal mucus production and exacerbates experimental enterocolitis - Stefan H. Oehlers; Maria Vega Flores; Christopher J. Hall; Kathryn E. Crosier; Philip S. Crosier (The Company of Biologists, 2012)
SUMMARY Exposure to retinoids for the treatment of acne has been linked to the etiology of inflammatory bowel disease (IBD). The intestinal mucus layer is an important structural barrier that is disrupted in IBD. Retinoid-induced alteration of mucus physiology has been postulated as a mechanism linking retinoid treatment to IBD; however, there is little direct evidence for this interaction. The zebrafish larva is an emerging model system for investigating the pathogenesis of IBD. Importantly, this system allows components of the innate immune system, including mucus physiology, to be studied in isolation from the adaptive immune system. This study reports the characterization of a novel zebrafish larval model of IBD-like enterocolitis induced by exposure to dextran sodium sulfate (DSS). The DSS-induced enterocolitis model was found to recapitulate several aspects of the zebrafish trinitrobenzene-sulfonic-acid (TNBS)-induced enterocolitis model, including neutrophilic inflammation that was microbiota-dependent and responsive to pharmacological intervention. Furthermore, the DSS-induced enterocolitis model was found to be a tractable model of stress-induced mucus production and was subsequently used to identify a role for retinoic acid (RA) in suppressing both physiological and pathological intestinal mucin production. Suppression of mucin production by RA increased the susceptibility of zebrafish larvae to enterocolitis when challenged with enterocolitic agents. This study illustrates a direct effect of retinoid administration on intestinal mucus physiology and, subsequently, on the progression of intestinal inflammation.